Sodium-glucose cotransporter 2 inhibitors and fracture risk in patients with type 2 diabetes mellitus: a meta-analysis of randomized controlled trials - Yake Lou; Ying Yu; Junchao Duan; Sining Bi; Khaing Nyein Chan Swe; Ziwei Xi; Yanan Gao; Yujie Zhou; Xiaomin Nie; Wei Liu (SAGE Publishing, 2020)
Background: Patients with type 2 diabetes mellitus (T2DM) have an increased risk of fracture compared with those without T2DM. Some oral glucose-lowering agents may increase the incidence of fracture. Whether sodium-glucose co-transporter 2 inhibitors (SGLT2is) are associated with increased risk of fracture remains unclear. Methods: We retrieved articles from PubMed, Embase, Cochrane Library database, and other sources up to 24 October 2019. We included randomized controlled trials (RCTs) that reported fractures and analyzed the fracture incidence of SGLT2i, canagliflozin, dapagliflozin, and empagliflozin. Subgroup analysis was also performed based on baseline characteristics. Results: A total of 78 RCTs with 85,122 patients were included in our analysis. The overall SGLT2i fracture incidence was 2.56% versus 2.77% in the control group [odds ratio (OR), 1.03; 95% confidence interval (CI) (0.95, 1.12); p  = 0.49]. Compared with the control treatment, treatment with canagliflozin led to a higher rate of fractures [OR, 1.17; 95% CI (1.00, 1.37); p  = 0.05], but no significant difference was observed when compared with dapagliflozin [OR, 1.02; 95% CI (0.90, 1.15); p  = 0.79] or empagliflozin [OR, 0.89; 95% CI (0.73, 1.10); p  = 0.30]. Subgroup analysis showed that, in a follow-up of less than 52 weeks, SGLT2i decreased the incidence of fracture by 29% [OR, 0.71; 95% CI (0.55, 0.93); p  = 0.01], but this benefit was lost when the follow-up extended to more than 52 weeks [OR, 1.08; 95% CI (0.98, 1.18); p  = 0.12]. Conclusion: Canagliflozin seems to increase the risk of fracture, while other SGLT2is do not result in a higher incidence of fracture.